2018
DOI: 10.1111/jfr3.12474
|View full text |Cite
|
Sign up to set email alerts
|

Mayors and “their” land: Revealing approaches to flood risk management in small municipalities

Abstract: The multilevel adaptive governance of flood risk reduction has been emphasised in the last decades and supported by the requirements of European Flood Directive (EC, 2007), while assigning an increasingly important role to municipalities. By contrast, only fragmented efforts have addressed the personal (expert knowledge), financial, and institutional limits of municipalities to achieve the flood risk management (FRM) goals. Starting with thorough literature review, we emphasise the key gaps in current understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Our assumption was that, in these areas, the relationship between individual action and FRM is closer than in urban centres (cf. Slavíková et al, 2019), which facilitate the risk perception approach of the study. In addition, it is assumed that their location outside of urban centres results in institutional distance from the national government, which may hinder the implementation of structural FRM measures (Consoer & Milman, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our assumption was that, in these areas, the relationship between individual action and FRM is closer than in urban centres (cf. Slavíková et al, 2019), which facilitate the risk perception approach of the study. In addition, it is assumed that their location outside of urban centres results in institutional distance from the national government, which may hinder the implementation of structural FRM measures (Consoer & Milman, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Lawrence, Quade, and Becker (2014) acquired similar evidence in New Zealand, and they also concluded that households affected by floods have a stronger preference for sharing responsibility with the central government. Some authors argue that reliance upon the national government results from a persisting preference for structural FRM measures and the limited financial and legal capacities of the local public and local governments to perform such measures (Figueiredo, Valente, Coelho, & Pinho, 2009; Slavíková, Raška, & Kopáček, 2019; Tunstall, Penning‐Rowsell, Tapsell, & Eden, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The mismatch is obvious at lowest administrative levels; for instance, where municipalities have gained fundamental (even though not sole) competencies in the past few decades (cf., the EU Floods Directive 2007/60/EC). Despite the arguments for the decentralization of FRM, it is now increasingly difficult to coordinate the ecologically relevant measures in catchments, which are fragmented across a number of administrative units (Moss and Newig 2010; Huesker and Moss 2015;Slavíková et al 2019) and diversified into various FRM strategies and practices (Gilissen et al 2016). The effects of land and institutional fragmentation will certainly differ for various flood types.…”
Section: Scale Mismatch In Socio-ecological Systemsmentioning
confidence: 99%
“…This raises a question about possible implementation barriers that may hamper the effort to reconcile the EU FRM strategies (see e.g. Slavíková, Raška, & Kopáček, 2018). The goal of this paper is to provide a comparative perspective on state flood recovery 1 funding for private damages in the so-called Visegrad Group Countries, i.e.…”
Section: Introductionmentioning
confidence: 99%